Implementasi Pembinaan Anggota Paskibraka Kota Palembang Tahun 2018 - Paripurna, Amir; Maulana, Maulana; Hendarso, Yoyok (Mahesa Research Center, 2024)
This article or writing aims to describe and analyze the implementation of Palembang City Paskibraka Member Development in 2018. The problem focuses on supporting and inhibiting factors in the implementation of Palembang City Paskibraka training. In order to approach this problem, a theoretical reference from George Edward III is used. Data was collected through interviews, observation and documentation and analyzed qualitatively. The research results show that communication in the implementation of Palembang City Paskibraka coaching in 2018 is quite good. The communication process, both internally and with related agencies, is running as expected, although it still needs improvement and evaluation to achieve more optimal performance previously. The implementation of Palembang City Paskibraka development in 2018 has followed clear standard operating procedures (SOP), and most policy implementers understand and comply with the procedures stated in the SOP. Apart from that, all employees who are policy implementers have a high commitment to the implementation of the 2018 Palembang City Paskibraka training. They work with dedication and full responsibility to achieve the desired goals and targets.